The Comparison Between Ideal Feminist and Discriminated Feminist From Characteristics of Amanda and Lauraas Seen In The Glass Menagerie Bytennesse Williams - Lestari Sembiring; Helmita Helmita (Jurnal Ilmiah Pendidikan Scholastic, 2019)
The problem in this thesis is the analysis of ideal feminist and discriminated feminist from the characteristics of Amanda and Laura is based on the three waves of feminist movements. Both Amanda and Laura represents the different kinds of feminist in literaty work, Amanda is the strong woman as the representation of ideal feminist, whereas Laura is the weak woman as the representation of discriminated feminist. Then, the purpose of research is to describe Laura as the discriminated feminist, Amanda as the ideal feminist, and to explain Laura and Amanda as the ideal and discriminated feminist from The Glass Menagerie.In research methodology, the data collection is performed through library research, which the writer gains the data and information about his object trought the books and other audiovisual equipment that related and relavant to the topic in the form of words or pictures. In the data analysis, it uses genetic structuralism, it looks the external factor of the literature that conveys the internal element of literary work such the actions of the main character, such as characters and author. The findings in this thesis can be seen from the characters of Amanda and Laura represents the different kinds of feminist in literaty work, Amanda is the strong woman as the representation of ideal feminist, whereas Laura is the weak woman as the representation of discriminated feminist. Amanda, a typical southern belle, trapped by the cruel reality, seeks comfort from her glorious past and causes her isolation from her life, which is the embodiment of her alienation. Laura, a fragile and terribly shy girl with a crippled leg, withdraws completely to her own world made of glass animals and eventually isolates from the society. It is her disability and the family environment cause her isolation from the society, which is just the embodiment of her alienation.